2014
DOI: 10.1007/s00704-014-1243-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of the temperature trends in Serbia during the period 1961–2010

Abstract: The spatial analysis of annual and seasonal temperature trends in Serbia during the period 1961-2010 was carried out using mean monthly data from 64 meteorological stations. Change year detection was achieved using cumulative sum charts. The magnitude of trends was derived from the slopes of linear trends using the least square method. The same formalism of least square method was used to assess the statistical significance of the determined trends. Maps of temperature trends were generated by applying a spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…When the EAO was in the positive phase, this depression moved towards the west of the UK and temperatures over Europe and Serbia were above normal. The results obtained in this study are in agreement with the Ta analysis for Serbia (Unkašević and Tošić, ; Bajat et al, ; Knežević et al, ). There is a statistically significant correlation between Tw and EAO for all gauging stations ( p < 0.05 ) (Table ).…”
Section: Discussionsupporting
confidence: 91%
“…When the EAO was in the positive phase, this depression moved towards the west of the UK and temperatures over Europe and Serbia were above normal. The results obtained in this study are in agreement with the Ta analysis for Serbia (Unkašević and Tošić, ; Bajat et al, ; Knežević et al, ). There is a statistically significant correlation between Tw and EAO for all gauging stations ( p < 0.05 ) (Table ).…”
Section: Discussionsupporting
confidence: 91%
“…Linear fit of the dataset for the maximum temperature shows an increasing trend for each of the seven stations in Serbia, for the period 1951-2010, which is in agreement with the results given by Bajat et al (2014). Figure 2a presents the maximum temperature time series for Vranje with statistically significant increasing trend (p value<0.0001 and Kendall's tau=0.034).…”
Section: Resultssupporting
confidence: 88%
“…Gocić and Trajković (2014) were analyzing the spatial and temporal patterns of precipitation in Serbia with the precipitation concentration index and performed the principal component analysis for the same time series. The spatial analysis of annual and seasonal temperature trends in Serbia during the period 1961-2010 was carried out by Bajat et al (2014) using the mean monthly data. The magnitude of the trends was derived from the slopes of linear trends using the least square method.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that the warming of the climate system is present in the Southeast Europe region. The annual and seasonal air temperature analyses in Serbia, Croatia, Slovenia, Montenegro, and Greece showed pronounced and mostly significant positive trends in vast majority of areas in the second half of 20th and the beginning of 21st century (Ducić, et al, 2009;Ducić, et al, 2008;Bajat, et al, 2015;Branković, et al, 2013;Milošević, et al, 2013;Burić, et al, 2014;Mamara, et al, 2016). The overall positive trends in annual air temperatures are mainly caused by the high and statistically significant positive summer trends.…”
Section: Introductionmentioning
confidence: 99%